Efficiency of semi-automated culture systems on microtubers formation of yam (Dioscorea alata L.) - Jova, MC. (Biotechnologie, Agronomie, Société et Environnement, 2012)
Yam clone 'Belep' in temporary immersion system showed favorable results on microtubers formation. Plants cultivated in this type of culture system were the first ones to initiate microtubers formation and produced the highest microtubers number per plant than with CIS (Constant Immersion System) and SLS (Static Liquid Medium System). These microtubers showed the greatest fresh and dry weights, as well as their diameters. In temporary immersion system, we obtained the highest total microtubers number and competent microtubers as planting material. Microtubers achieved in this type of culture system were distinguished by their quality expressed in the higher dry matter content and starch concentration. In order to carry renewals of culture media and to maintain continuous culture growing for direct planting material, knowledges on preferences and ion depletion in culture medium during microtubers formation in yam cultivated in temporary immersion system were acquired.